Hand motor recovery after stroke: tuning the orchestra to improve hand motor function - Fregni, Felipe; Pascual-Leone, Alvaro (Cognitive and behavioral neurology, 2006)
The motor deficits after stroke are not only the manifestation of the injured brain region, but rather the expression of the ability of the rest of the brain to maintain function. After a lesion in the primary motor cortex, parallel motor circuits might be activated to generate some alternative input to the spinal motoneurons. These parallel circuits may originate from areas such as the contralateral, undamaged primary motor area, bilateral premotor areas, bilateral supplementary motor areas, bilateral somatosensory areas, cerebellum, and basal ganglia. Most importantly, the efferent, cortico-spinal output pathways must be preserved for a desired behavioral result. Most of the recovery of function after a stroke may represent actual relearning of the skills with the injured brain. The main neural mechanisms underlying this relearning process after stroke involve shifts of distributed contributions across a specific neural network (fundamentally the network engaged in skill learning in the healthy). If these notions are indeed correct, then neuromodulatory approaches, such as transcranial magnetic stimulation, targeting these parallel circuits might be useful to limit injury and promote recovery after a stroke. This paper reviews the stroke characteristics that can predict a good recovery and compensations across brain areas that can be implemented after a stroke to accelerate motor function recovery.